Expression of CA-IX is associated with advanced stage tumors and poor survival in oral squamous cell carcinoma patients - Pérez-Sayáns, Mario; Suárez-Peñaranda, José Manuel; Pilar, Gayoso-Diz; Supuran, Claudiu T.; Pastorekova, Silvia; Barros-Angueira, Francisco; Gándara-Rey, José Manuel; García-García, Abel (Journal of oral pathology & medicine, 2012)
J Oral Pathol Med (2012) Introduction:  Carbonic anhydrases (CAs), a group of ubiquitously expressed metalloenzymes, are involved in numerous physiological and pathological processes, including tumorigenicity. Specifically, CA‐IX has been primarily found in hypoxic tumor tissues. Material and methods:  This is a retrospective study of tumors from the Tissue Bank of the Pathology Department of the University Hospital of Santiago de Compostela. We selected 50 oral squamous cell carcinomas (OSCCs) using Tissue Microarray (TMA) technology. The immunohistochemical study was performed to determine CA‐IX expression. The resulting data were subject to statistical analysis and survival curves. Results:  Of the 50 cases, 23 were detected in early stages (I and II) and 27 in advanced stages (III and IV). In the first year, almost 50% of patients in stages III–IV died, which contrasted with those patients in initial stages who registered a survival rate of 80% (P = 0.019). Regarding the expression of CA‐IX, nine cases (18%) were negative, 18 cases (36%) were moderate, while 23 cases (46%) were intense. Tumors in stages I‐II showed a positivity of 52.6%; however, in advanced stages, the percentage reached 95.5% (P = 0.002). Regarding CA‐IX expression and survival, patients with tumors with strong staining had a lower average survival time (13.8 months) than patients with negative or weak‐moderate staining (33.4 and 32.8 months, respectively), log‐rank = 6.1, P value = 0.0484. Conclusions:  Early diagnosis of these tumors is essential to improve patient survival. CA‐IX expression augments with increasing tumor stage, probably related with the degree of hypoxia; thus, its measurement can be used as a prognostic factor.